President's Message: Yes — We Do Make A Difference - Hay, Vija (Operating Room Nurses Association of Canada Journal, 1996)
The question, “Are Registered Nurses making a Difference” is not new, but it is being asked more frequently and louder. The Canadian Nurses Association Biennial Convention in June is titled “Nurses Make the Difference - Ask a Nurse”. At the recent Operating Room Nurses Association of Ontario Provincial Conference in Toronto a large focus group analysed the question of why do we need a Registered Nurse in the Operating Room.